2013
DOI: 10.1149/2.059310jes
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: An Experimental Study of the Effects of Operational History on Activity Changes in a PEMFC [J. Electrochem. Soc.,160, F1067 (2013)]

Abstract: On page F1068 Table I. should be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Jomori et al. [ 149 ] studied the effects of low humidity operation on a 1 cm 2 cell, where the cell was left to operate for 18 h at a 20% RH. Using the current density achieved at 0.9 V after 200 s as a benchmark, they found that after 13 h of operating at low humidity, the normalized activity level of the cell had dropped by 68% when compared to the activity measured immediately after the cell's activation.…”
Section: Catalyst Layer Performance Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Jomori et al. [ 149 ] studied the effects of low humidity operation on a 1 cm 2 cell, where the cell was left to operate for 18 h at a 20% RH. Using the current density achieved at 0.9 V after 200 s as a benchmark, they found that after 13 h of operating at low humidity, the normalized activity level of the cell had dropped by 68% when compared to the activity measured immediately after the cell's activation.…”
Section: Catalyst Layer Performance Characterizationmentioning
confidence: 99%
“…This effect is more extreme under low humidity conditions, suggesting further mechanisms of ionomer change were occurring. [ 297 ] Ionomer sulfonic acid group adsorption to the Pt surface reduces the number of electrochemically active Pt sites, and the ionomer backbone forming a continuous layer can prohibit oxygen transport. [ 61,235,298 ] High WU in high RH conditions is suspected to mitigate Pt poisoning as the degree of sulfonic acid adsorption decreases with increased interfacial water.…”
Section: Ionomer Distributionmentioning
confidence: 99%